Expression of interferon-gamma, interferon-alpha and related genes in individuals with Down syndrome and periodontitis - Tanaka, Marcia H. [UNESP]; Giro, Elisa M. A. [UNESP]; Cavalcante, Licia B. [UNESP]; Pires, Juliana R.; Apponi, Luciano H. [UNESP]; Valentini, Sandro Roberto [UNESP]; Spolidorio, Denise M. P. [UNESP]; Capela, Marisa Veiga [UNESP]; Rossa, Carlos [UNESP]; Scarel-Caminaga, Raquel M. [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2012)
Background: Recently, attenuation of anti-inflammatory and increase of pro-inflammatory mediators was demonstrated in individuals with Down syndrome (DS) in comparison with euploid patients during periodontal disease (PD), suggesting a shift to a more aggressive inflammation in DS.Aim: To determine the influence of DS in the modulation of interferons (IFNs) signaling pathway in PD.Materials and methods: Clinical periodontal assessment was performed and gingival tissue samples obtained from a total of 51 subjects, including 19 DS individuals with PD, 20 euploid individuals with PD and 12 euploid individuals without PD. Expression levels of interferon-gamma (IFNG) and interferon-alpha (IFNA), and their receptors IFNGR1, IFNGR2, IFNAR1 and IFNAR2, the signaling intermediates Janus kinase 1 (JAK1), signal transducer and activator of transcription 1 (STAT1) and interferon regulatory factor 1 (IRF1) were determined using real time quantitative polymerase chain reaction (qPCR).Results: Clinical signs of periodontal disease were markedly more severe in DS and euploid patients with PD in comparison to euploid and periodontally healthy patients. There was no difference on mRNA levels of IFNA, IFNG, INFGR2, IFNAR1 and IFNAR2 between DS and euploid individuals, even though some of these genes are located on chromosome 21. STAT1 and IRF1 mRNA levels were significantly lower in DS patients in comparison with euploid individuals with PD. In euploid individuals, PD was associated with an increased expression of IFNGR1, IFNGR2, IFNAR1, STAT1 and IRF1.Conclusions: Reduced expression of STAT1 and IRF1 genes indicate an impaired activation of IFNs signaling in individuals with DS and PD. Expression of IFNA, IFNG and IFN receptors was not altered in DS patients, indicating that indirect mechanisms are involved in the reduced activation of IFN signaling. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Gene expression; Inflammation; Periodontitis; Cytokines; Down syndrome